Thermodynamic assessments of the Sn-In and Sn-Bi binary systems - Lee, BJ; Oh, CS; Shim, JH (MINERALS METALS MATERIALS SOC, 1996)
A thermodynamic evaluation of the Sn-In and Sn-Bi system has been made by using thermodynamic models for the Gibbs energy of the individual phases. An optimized set of thermodynamic parameters was obtained taking into consideration relevant experimental information. The thermodynamic parameters of the Sn-In and Sn-Bi systems and comparisons between calculation and experimental data are presented.
Keywords: LEAD-FREE SOLDERS; ALLOYS